Ciclos creativos en la poesía de James Joyce - Álvarez Amorós, Jose Antonio (Miscelánea: A Journal of English and American Studies, 1992)
This essay attempts to distinguish between two considerably different creative impulses within Joyce’s poetry that give rise to his book Chamber Music [1907] and Pomes Penyeach (1927). We analyse the former as a conscious and youthful effort on Joyce’s part to make his name as a poet. Hence, his care for style, contrived versification, purity of diction, and impersonality under the welcome influence of the Elizabethan collections of lyrical verse, Shakespeare’s dramatic work, and the biblical Song of Songs. After twenty years of struggle and some bitter disappointments, Joyce’s poetical mood altered noticeably. Pomes Penyeach is not the result of an intent purpose to compose a’ systematic book, but rather a collection of occasional poems directly derived from his experience. His formal rigour also relaxed, and personal confession replaced stylistic aloofness. In conclusion, both books seem to be poles apart, save for a common denominator: the stubborn intensity with which they incorporate material borrowed from Shakespeare, the Bible, Dante, Nashe, and others.